Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/pro.4078
|View full text |Cite
|
Sign up to set email alerts
|

Criticality of a conserved tyrosine residue in the SpeG protein from Escherichia coli

Abstract: The SpeG spermidine/spermine N-acetyltransferase (SSAT) from Escherichia coli belongs to the Gcn5-related N-acetyltransferase (GNAT) superfamily of proteins. In vitro characterization of this enzyme shows it acetylates the polyamines spermine and spermidine, with a preference toward spermine. This enzyme has a conserved tyrosine residue (Y135) that is found in all SSAT proteins and many GNAT functional subfamilies. It is located near acetyl coenzyme A in the active center of these proteins and has been suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Therefore, if the ∆ rv1877 mutant still displays a sensitivity towards Spm despite the upregulation of rv3065 (that is supposed to detoxify Spm), then Rv1877 is indeed involved in the detoxification of Spm, though it is not the only protein involved (explaining the low sensitivity). Compensation can also occur by other mechanism of Spm inactivation/detoxification such as acetylation by SpeG as reported in other bacteria ( Limsuwun and Jones, 2000 ; Filippova et al, 2019 ; Le et al, 2021 ; Kumar et al, 2022 ). In our previous studies, we found that M.tb has a SpeG ortholog that is Rv3034c ( Sao Emani and Reiling, 2023 ).…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, if the ∆ rv1877 mutant still displays a sensitivity towards Spm despite the upregulation of rv3065 (that is supposed to detoxify Spm), then Rv1877 is indeed involved in the detoxification of Spm, though it is not the only protein involved (explaining the low sensitivity). Compensation can also occur by other mechanism of Spm inactivation/detoxification such as acetylation by SpeG as reported in other bacteria ( Limsuwun and Jones, 2000 ; Filippova et al, 2019 ; Le et al, 2021 ; Kumar et al, 2022 ). In our previous studies, we found that M.tb has a SpeG ortholog that is Rv3034c ( Sao Emani and Reiling, 2023 ).…”
Section: Discussionmentioning
confidence: 76%
“…However, we searched and found Rv3170 (putative flavin-containing monoamine oxidase AofH) and Rv1751 (probable oxidoreductase) as the closest orthologs to the eukaryotic SPO when blasted against the M.tb proteome. Acetylation of Spm by SpeG and excretion of the acetylated product are another route used by Escherichia coli ( 47 , 51 53 ) to detoxify Spm and Spd. We found that the closest ortholog of E. coli SpeG in M.tb is Rv3034c ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…40 In addition to GLO1, we also found that speG displayed upregulation in ESBLs-EC compared to susceptible Escherichia coli , which is at least partially consistent with the results from recent two studies. 41 , 42 In the future, we will continue with the study with other three upregulated genes.…”
Section: Discussionmentioning
confidence: 99%